The controversial universality of individual human rights - Graf, Friedrich Wilhelm (Verbum et ecclesia, 2005)
Human rights is currently a very relevant but also very controversial issue in international politics in the aftermath of some of the events that occurred during the twentieth century. In this article, the author puts the present issues in perspective by initiating the discussion with a look at aspects of the historical development of the concept of human rights. He then moves on to take a closer look at how the concept of human rights feature and function in the Christian religion and follows that up with an overview of how human rights are perceived and are operative in the religion of Islam. The article concludes with a focus on inter-cultural discourse.